Dr. Seuss's How the Grinch Stole Christmas! - Jones, Chuck; Karloff, Boris (Warner, 1999)
Jones is perhaps the single greatest contributor to the Warner Brothers animation library, bringing to life a plethora of characters such as Bugs Bunny, Daffy Duck, and Yosemite Sam, among many others. Jones' simplistic yet expressive animation style is evident throughout "How the Grinch Stole Christmas," and I'm not sure anyone else could have done as commendable a job as Jones. Within half an hour Jones takes a tale and develops comedy and a deep moral of the meaning of Christmas to contribute to this classic. [www.dvdverdict.com]